2015
DOI: 10.1021/acs.est.5b02947
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Efficiency of Chlorine Disinfection of Naegleria fowleri in a Drinking Water Distribution Biofilm

Abstract: Naegleria fowleri associated with biofilm and biological demand water (organic matter suspended in water that consumes disinfectants) sourced from operational drinking water distribution systems (DWDSs) had significantly increased resistance to chlorine disinfection. N. fowleri survived intermittent chlorine dosing of 0.6 mg/L for 7 days in a mixed biofilm from field and laboratory-cultured Escherichia coli strains. However, N. fowleri associated with an attached drinking water distribution biofilm survived mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 37 publications
0
42
0
1
Order By: Relevance
“…; Miller et al . ). In general, the efficacy of disinfectants for OPs are only transient, due to their regrowth within biofilm (Wéry et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Miller et al . ). In general, the efficacy of disinfectants for OPs are only transient, due to their regrowth within biofilm (Wéry et al .…”
Section: Discussionmentioning
confidence: 97%
“…It is well understood that planktonic cells are well controlled by residual disinfectants (e.g. chlorine dioxide, 0Á5 mg l À1 ; chlorine, 2Á5 mg l À1 ; monochloramine, 0Á5 mg l À1 ; and copper-silver ionization, 0Á8/0Á02 mg l À1 ), but biofilm and amoeba-bound cells are much more resistant to such treatments (Buse et al 2012;Miller et al 2015). In general, the efficacy of disinfectants for OPs are only transient, due to their regrowth within biofilm (W ery et al 2008a) and following loss of any biocide residual (Kilvington and Price 1990;Thomas et al 2004).…”
Section: The Occurrence Quantity and Variations Of Opportunistic Patmentioning
confidence: 99%
“…Recycled waters have complex microbial communities and high availability of nutrients and other organic matter, creating optimal conditions for biofilm establishment. 170 Recent studies have also shown increased chlorine resistance of FLA in the presence of naturally established biofilm 171,172 and even non-biofilm Vermamoeba spp. have been observed to resist chlorination.…”
Section: Amoebaementioning
confidence: 99%
“…rate and extend of formation) in drinking water distribution systems. Additionally, use of this device has been further extended to investigate occurrences of discoloured water [7] and pathogenic organisms [33] in drinking water distribution systems. Unlike the MRD, this offline monitor is cost effective and is easy to install to facilitate routine biological and chemical assessment of drinking water distribution systems.…”
Section: Introductionmentioning
confidence: 99%